Examining the Link Between Future Prospects and Intentions to Have Children - Kwan, Da Eun; Choi, Seulki (Journal of Policy Studies, 2023)
What motivates individuals to have children? As the ongoing rapid fertility decline in South Korea spurs serious social concerns, there arises an urgency to enhance a better understanding of the family formation motivation. While much of the existing discussions focus on economic conditions or structural constraints as major obstacle in childbearing decision, a burgeoning body of research emphasizes the importance of the subjective perception aspect. There can be hardly a disagreement on the significance of future prospects in family formation motivation, yet the empirical evidence is surprisingly lacked. To fill this niche, this study aims to assess the link between the prospect for the next generation and individuals’ fertility desire. Employing the online survey on 1,198 individuals aged between 25 and 49, this study examines the correlation between the future prospects and childbearing desire. The analysis results reveal a positive correlation, and, in particular, positive future prospect is observed to moderate the association between the household income level and fertility desire. This study is expected to shed a light to better understanding of the low fertility in Korea, providing suggestive evidence of the perceived intergenerational social mobility in childbearing decision. We suggest that the fundamental policy goal should be to convict individuals of the promising future for the next generation.